RANCANG BANGUN APLIKASI PENGELOLAAN PENGADUAN PELANGGAN BERBASIS WEBSITE PADA PLN ULP AMPERA - Ilmia Tanjung; Irfan Dwi Jaya (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The development of digital technology encourages public service companies to improve the quality of customer service. PT PLN (Persero), as Indonesia’s national electricity service provider, faces challenges in managing customer complaints that are still handled conventionally through direct visits and phone calls, resulting in delays in complaint handling and a lack of service information transparency. This study aims to design and develop a web -based customer complaint management application called SuaraQita using the CodeIgniter 3 framework at PLN Unit Layanan Pelanggan (ULP) Ampera.The research method used is the System Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and system testing. Data collection techniques were carried out through observation, interviews, and literature studies, while system testing used the Black Box Testing method. The results of this study indicate that the SuaraQita application can facilitate customers in submitting complaints and monitoring complaint status online, as well as assist officers in managing complaints more effectively and systematically. Based on the testing results, all system features functioned according to user requirements. The conclusion of this study shows that the implementation of a web based customer complaint management application can help improve customer service quality and support digital transformation at PLN Unit Layanan Pelanggan Ampera.